2002
DOI: 10.1111/j.1751-0813.2002.tb10971.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of copper heptonate with copper oxide wire particles as copper supplements for sheep on pasture of high molybdenum content

Abstract: In sheep on pasture of high Mo content a single intramuscular injection of CuHep providing 37.5 mg Cu to adults or 25 mg Cu to weaners will raise liver Cu reserves for at least 9 and 3 months respectively and may be an acceptable alternative to COWP for preventing seasonal Cu deficiency in sheep in southern Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…No clinical signs of toxicity were apparent in Swaledale ewes given IM injections of CuHep at dosages of 3 to 4 mg Cu/kg body weight 6 or in Dormer, South African Mutton Merino or Merino sheep given CuHep subcutaneously at dosages up to 3 mg Cu/kg body weight or intravenously at dosages up to 0.6 mg Cu/kg body weight. 4 We found that a single IM injection of CuHep at a dosage of about 0.7 mg Cu/kg body weight raised liver Cu reserves for up to 9 months in mature Merino sheep grazing pasture of high molybdenum (Mo) content 7 and suggested that increasing the dosage to 1 mg Cu/kg body weight would pose little risk of toxicity. In practice, the treatment of a flock may result in doses of CuHep greater than 1 mg Cu/kg body weight being administered to sheep with normal liver Cu reserves.…”
Section: Cuhepmentioning
confidence: 99%
See 3 more Smart Citations
“…No clinical signs of toxicity were apparent in Swaledale ewes given IM injections of CuHep at dosages of 3 to 4 mg Cu/kg body weight 6 or in Dormer, South African Mutton Merino or Merino sheep given CuHep subcutaneously at dosages up to 3 mg Cu/kg body weight or intravenously at dosages up to 0.6 mg Cu/kg body weight. 4 We found that a single IM injection of CuHep at a dosage of about 0.7 mg Cu/kg body weight raised liver Cu reserves for up to 9 months in mature Merino sheep grazing pasture of high molybdenum (Mo) content 7 and suggested that increasing the dosage to 1 mg Cu/kg body weight would pose little risk of toxicity. In practice, the treatment of a flock may result in doses of CuHep greater than 1 mg Cu/kg body weight being administered to sheep with normal liver Cu reserves.…”
Section: Cuhepmentioning
confidence: 99%
“…Plasma samples were assayed for TCA-soluble Cu by atomic absorption spectrophotometry (GBC 906 Flame Atomic Absorption Spectrophotometer). 7 Using commercially available kits and a Cobas Mira random access analyser (F Hoffmann La Roche & Co) the rates of reduction of NADP and NAD were used to measure plasma creatine kinase (Trace Scientific Ltd, Melbourne) and glutamate dehydrogenase (E Merck, Darmstadt, Germany) activities, respectively.…”
Section: Sample Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, in Mo excessive use, livestock and poultry are prone to toxic reactions. 2 Mo is also a severe environmental pollutant. 3 The Mo content in soil was found to be as high as 77 mg/kg in a site in Armenia.…”
Section: Introductionmentioning
confidence: 99%